2020
DOI: 10.26434/chemrxiv.12885476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biosynthesis of Chlorinated Lactylates in Sphaerospermopsis sp. LEGE 00249

Abstract: Lactylates are an important group of molecules in the food and cosmetic industries. A series of natural halogenated 1-lactylates – chlorosphaerolactyaltes (<b>1</b>-<b>4</b>) – were recently reported from <i>Sphaerospermopsis</i> sp. LEGE 00249. Here, we identify the <i>cly</i> biosynthetic gene cluster, containing all the necessary functionalities to generate and release the natural lactylates. Using a combination of stable isotope-labeled precursor feeding and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In our previous study, 6 nocuolactylates were found to incorporate three alkyl moieties derived from either hexanoic acid or longer fatty acids. The lactylate portion of these molecules accounts for one such incorporation, 12 indicating that the two remaining moieties are used for the biosynthesis of 1. We considered that these building blocks could be used to generate the C13 alkyl moiety of 1.…”
Section: Annotation Of the Noc Gene Products And Acyl-acp Dehydrogena...mentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, 6 nocuolactylates were found to incorporate three alkyl moieties derived from either hexanoic acid or longer fatty acids. The lactylate portion of these molecules accounts for one such incorporation, 12 indicating that the two remaining moieties are used for the biosynthesis of 1. We considered that these building blocks could be used to generate the C13 alkyl moiety of 1.…”
Section: Annotation Of the Noc Gene Products And Acyl-acp Dehydrogena...mentioning
confidence: 99%
“…The latter has been implicated in the biosynthesis of the chlorosphaerolactylates and was predicted to activate dodecanoic acid, but also decanoic and tetradecanoic acids to a minor extent. 12 We heterologously expressed and purified each FAAL as well as with their cognate ACPs in E. coli. NocH contains both FAAL and ACP domains and was expressed as a single polypeptide, while ClyA and its associated ACP ClyB were expressed and purified separately.…”
Section: Noch Activates Hexanoic and Octanoic Acidsmentioning
confidence: 99%
See 2 more Smart Citations